ANALISA TEKNIS DAN EKONOMIS PEMANFAATAN PLTS OFF-GRID PADA SISTEM KENDALI TINGGI MUKA AIR PADA TANDON DI SEKAR ANUGERAH PENGLIPURAN - Fadlikha Ramadhan, Fikri; Elba Duta Nugraha, I Putu; Janardana, I Gusti Ngurah (Program Studi Teknik Elektro UNUD, 2024)
To fulfill thel daily need for clean water, it is necessary to expand the water supply system to reduce the risk of uncontrolled water use. Water Level Control (WLC) is a control system that can control water capacity according to what is required automatically. The design of the Off-Grid PLTS in Sekar Penglipuran as an energy supplier for the water level control system in the reservoir and the start of the pump in the reservoir. Utilization of PLTS in the operation of water level control systems in reservoirs as well as knowing the power generated and component requirements as well as the feasibility of investing in Off-Grid PLTS. This research includes the design of Off-Grid PLTS by analyzing technically and economically. The results of this research are that the Off-Grid PLTS design is estimated to be able to produce power for the control system needs of 525.76 Wp and can produce an energy yield of 932.575 kWh/year with a performance ratio of 85%. Designing a PLTS requires an initial investment cost of Rp. 70,330,605,- with an NPV of -Rp. 65,668,939,506,- so based on economic aspects, designing an Off-Grid PLTS is not worthy of investment.